OPTOELECTRONIC DEVICE FOR MEASURING THE HUMIDITY OF SILKWORTH COCOONS - Kuldashov G.O; Nabiev D.O (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
The goal of this work was to create an optoelectronic device for measuring the humidity of silkworm cocoons based on mid-IR LEDs. An optoelectronic device has been developed for measuring the humidity of silkworm cocoons based on mid-IR LEDs, allowing measurements in real mode with an accuracy of 1.5%. In the optoelectronic device for measuring the humidity of silkworm cocoons, LEDs with emission spectra of 2.2 μm are used as a reference channel, and LEDs with emission spectra of 1.94 μm are used as a measuring channel. A scheme is proposed that ensures the main condition of two-wave optoelectronic devices, the temporal and temperature stability of the LED parameters and the equality of their initial reference, measuring radiation fluxes, which determine the measurement accuracy.